Insights into the dynamics of the 2010 Eyjafjallajokull eruption using seismic interferometry and network covariance matrix analyses - /Caudron, Corentin; Soubestre, J.; Lecocq, T.; White, R. S.; Brandsdottir, B.; Krischer, L. (2022)
Applying seismic interferometry and network covariance matrix-based analyses to detect and locate the source of volcanic tremor during the 2010 Eyjafjallajokull effusive flank and explosive-effusive summit eruptions has provided new insights into this iconic event. The tremor source locations derived from the network covariance matrix approach were spatially distinct during the two eruptions. The tremor was radiated between the surface and 5-6 km depth during the effusive flank eruption, including an apparently progressive upward migration in early April 2010, but was strictly confined to the surface during the summit eruption. Each phase of the summit eruption left a distinct fingerprint in the seismic records. Effusive phases radiated continuous tremor between 0.6 and 5 Hz, whereas explosive phases produced tremor in a more pulsating fashion over a wider frequency band (0.2-10 Hz). A period of intermittent tremor bursts (called banded tremor) on 15 April, associated with formation of a new vent at the summit, was most likely generated by magma-gas-meltwater interaction within a subglacial enclosure. The banded tremor ceased following an abrupt draining of the newly formed subglacial cauldron, resulting in a large slurry glacial meltwater flood (jokulhlaup). This study highlights the importance of new data processing methodologies for future monitoring of volcanic tremor in real-time.